Thermo-responsive transfection of DNA complexes with well-defined chitosan terpolymers - Bao, Hongqian (2013)
Serial thermo-sensitive CS(-g-PDMAEMA)-g-PNIPAM terpolymers (termed as TCS) were prepared by atom transfer radical polymerization (ATRP) and click reactions, where CS, PDMAEMA, and PNIPAM stand for chitosan, poly((2-dimethylamino)ethyl methacrylate), and poly(N-isopropylacrylamide) respectively. Their lower critical solution temperature (LCST) determined by laser light scattering (LLS) was around 32.5–35.1 °C. The incorporation of CS and PNIPAM considerably decreased the cytotoxicity of PDMAEMA. Gel electrophoresis and TEM results revealed that the association and dissociation of TCS/DNA complexes could be tuned by varying temperature. The transfection level of TCS and controls was evaluated with COS7 and HeLa cells using two different reporter genes, pRL-CMV encoding luciferase and pEGFP-N1 encoding green fluorescence protein (GFP). The transfection efficiency of one specific terpolymer (TCS4) incubated at 37 °C for 22 h, 20 °C for 2 h and 37 °C for 24 h increased 1–4 fold compared to that incubated at 37 °C for 48 h. Encouragingly, at optimum N/P ratios, the transfection efficiency of TCS was comparable or superior to that of “gold-standard” PEI (25 kDa).